HTO – A complementary ergonomics approach. (March 2017) - Karltun, Anette; Karltun, Johan; Berglund, Martina; Eklund, Jörgen
Abstract: The field of human factors and ergonomics constitutes a strong potential in systems analysis, design and improvement. However, it is difficult to communicate its potential value. This paper addresses how the human-technology-organization (HTO) concept can be defined and supports the understanding, communication and development of the systems' character and potential of human factors and ergonomics. Empirical examples from the authors' experiences of working with the HTO concept in R&D and teaching are illustrated, including its usefulness as: 1) a conceptual model; 2) an analysis framework; 3) a meta methodology; 4) a pedagogical tool; and 5) a design tool. The use of HTO provides guidance on how the system can be designed to better support health, individual and systems performance. It is further suggested that there is a strong potential for developing the theory, applications and methodological aspects of HTO. Highlights: The HTO concept is useful as a framework for analysis and design of work systems. The HTO concept is based on a systems approach and emphasizes human interactions. The HTO concept introduces the human as a separate sub-system of the work activity. The HTO concept guides design efforts to include health and wellbeing. HTO as a concept is intuitively attractive to business stakeholders and students.